Investigations on Temperature and Cultivar Variability in Microbial Dynamics and Enzyme Activity in Sweet Potato Rhizospheres - Devotha Mwazembe; D.G. Mortley; R. Shange; R, O, Ankumah; O. Idehen; J. Quansah; S. Fall; V. S. Santhosh Mithra (Geography, Earth Science and Environment: Research Highlights Vol. 8, 2025)
Background: Sweet potato [Ipomea batatas (L.) Lam.] is an important root crop known for its nutritional, medicinal, industrial and economic values. It is the fourth most important root crop in terms of the quantity of production and ranks seventh in global food production. Aim: To determine the influence of temperature on sweet potato yield, soil enzyme activity and composition of the microbial community in the rhizosphere during early growth stage-65DAP. Methodology: The study was conducted as a Completely Randomized Design with a 2x2 factorial treatment arrangement of two temperatures and two cultivars —and four replications in time. The research took place at George Washington Carver Agricultural Experiment Station, Tuskegee University, Tuskegee Alabama, between February to December 2022. Two sweet potato cultivars, Beauregard and Whatley/Loretan, were planted and exposed to high (32/26°C) and optimal (28/22°C) diurnal temperatures in a plant growth chamber. Standard cultural practices for irrigation and fertilizer application were followed. The plants were harvested 65 days after planting (65 DAP) and rhizosphere samples from both cultivars were collected. The microbial composition, including bacterial 16S rDNA and fungal ITS (Internal Transcribed Spacer), was analyzed using a standard DNA-Based Quantitative Technique The extracellular enzymes, Acid Phosphatases (P-acid), \(β\)-Glucosidase (GLU), N-acetylglucosaminidase (\(β\)-NAG) and phosphodiesterase (DIEST) were analyzed using fluorometric microplate enzyme assays. Results: Bacterial communities were dominated by phyla Acidobacteria and Proteobacteria, whereas fungi were dominated by the Ascomycota across the samples. Temperature significantly affected the abundance of some bacterial phyla (Proteobacteria, Firmicutes, Verrucomicrobia and Chloroflexi) and all identified fungal phyla (Ascomycota, Mucoromycota, and Entomophthoromycota). Cultivars affected bacterial Phylum Gemmatimonadetes and fungi phyla Mucoromycetes and Ascomycota, with their higher relative abundances found in Whatley/Loretan than in Beauregard. There were significant interactions between temperature and cultivars for bacteria phyla Acidobacteria, Verrucomicrobia, Firmicutes and Fungi Entomophthoromycota. Additionally, high temperatures influenced the activities of key soil enzymes—acid phosphatase, \(β\)-glucosidase, and \(β\)-1,4-N-acetylglucosaminidase—in the rhizosphere of sweet potato, irrespective of cultivars. Conclusion: The bacterial and fungal populations and activities of key soil enzymes in the rhizosphere of Whatley/Loretan and Beauregard sweet potato cultivars were significantly impacted by high temperatures. These enzymes play a crucial role in the decomposition of organic matter, as well as phosphorus (P), nitrogen (N), and carbon (C) cycling, thereby regulating nutrient availability for plant uptake.